2017
DOI: 10.3389/fncel.2017.00377
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nitric Oxide Synthase Contributes to PTZ Kindling Epilepsy-Induced Hippocampal Endoplasmic Reticulum Stress and Oxidative Damage

Abstract: Epilepsy is one of the most common chronic neurological disorders which provoke progressive neuronal degeneration. Endoplasmic reticulum (ER) stress has recently been recognized as pivotal etiological factors contributing to epilepsy-induced neuronal damage. However, the specific contribution of epilepsy made to ER stress remains largely elusive. Here we use pentylenetetrazole (PTZ) kindling, a chronic epilepsy model, to identify neuronal nitric oxide synthase (nNOS) as a signaling molecule triggering PTZ kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 47 publications
6
35
1
1
Order By: Relevance
“…22 For instance over generation of superoxide anion in the hippocampus of kindled mice by PTZ was reported. 5 In another example, thiol groups including glutathione (GSH) and glutathione disulfide (GSSG) decreased in the cerebral cortex of mice when they were kindled by PTZ. 23 Researchers also reported that enhanced level of intracellular Ca 2+ as a result from activation of inotropic glutamate receptors during abnormal neuronal excitations leads to uncontrolled production of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 For instance over generation of superoxide anion in the hippocampus of kindled mice by PTZ was reported. 5 In another example, thiol groups including glutathione (GSH) and glutathione disulfide (GSSG) decreased in the cerebral cortex of mice when they were kindled by PTZ. 23 Researchers also reported that enhanced level of intracellular Ca 2+ as a result from activation of inotropic glutamate receptors during abnormal neuronal excitations leads to uncontrolled production of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, seizures followed by PTZ administration have been propounded as an important cause of oxidative status imbalance in some brain areas including hippocampus. 5 For example, PTZ infusion associated with the sever stimulation of N-Methyl-Daspartate (NMDA) receptors has been shown to elevate the level of free radicals such as nitric oxide (NO) and peroxynitrite in the brain of rats. 6 On the other hand, the antioxidant properties of angiotensin-converting enzyme (ACE) inhibitors have been accepted.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Zhu ve ark. [31] (2017) nöronal NOS, PTZ-kindling ile indüklenen epilepside ER stresini ve oksidatif hasarı tetikleyen bir sinyal molekülü olarak tanımlanmaya çalışmış, nöronal NOS'un hipokampal ER stresini ve oksidatif hasarı tetiklemek için reaktif azot türlerinin önemli bir üyesi olan peroksinitrit yoluyla etki ettiğini göstermiştirler. Kronik epilepsinin neden olduğu ER stres ve oksidatif hasar için özel bir mekanizma ve kronik epilepsi hastalarında potansiyel bir terapötik hedef olabileceği belirtilmiştir.…”
Section: Discussionunclassified
“…According to the method 45 , PTZ (35 mg/kg) was administered to the mice by intraperitoneal (i.p.) injection every other day for 30 days.…”
Section: Methodsmentioning
confidence: 99%